Renewable Energy, Environment and GDP in High-Income Countries: Evidence from Europe - Boudiaf Hafid (Economics and Business)
The research paper considers the dual role of renewable energy in achieving environmental safety and promoting economic growth. The ARDL methodology was applied to data collected from high-income countries in Europe in the period 1990–2020.The results showed that there was a positive and strong effect of renewable energy on reducing CO2 emissions in the long term, but its effect in the short term was weak. Fossil energy and economic growth positively affected the increase in emissions. Likewise, the expected role of renewable energy in promoting economic growth was partially achieved in the short term, but was not achieved in the long term. The study encouraged the efforts of European countries to promote and accelerate the transition towards renewable energy in order to promote environmental safety and achieve energy independence from abroad.